Endogenous choice of minority shareholdings: Effects on product market competition - Samuel de Haas (Philipps-University Marburg, School of Business and Economics, 2019)
Non-controlling minority shareholdings in rivals (NCMS) lower the sus- tainability of collusion under a wide variety of circumstances. Nevertheless, NCMS are sometimes deemed to facilitate collusion, in particular if the level of NCMS is exogenous. The present paper endogenizes firms' choice of NCMS and answers the question: Would colluding firms find it rational to acquire NCMS in rivals? The study of the acquisition reveals that firms have an in- centive to acquire NCMS which are accompanied by a shift from collusive to competitive behaviour.
Keywords: G34; K21; L41; 330; Collusion; Coordinated Effects; Minority Shareholdings; Merger Control; Unilateral Effects